Shining Lights on Limits: Optimizing Luminescent Solar Concentrators for Solar Windows - Thomas A. de Bruin; Wilfried G. J. H. M. van Sark (Advanced Photonics Research)
The luminescent solar concentrator (LSC) can function as an electricity‐generating window whose performance is hindered by an inherent trade‐off between power conversion efficiency and visible light transmission. To optimize this trade‐off, a numerical algorithm is used to find the power conversion efficiency of 92 luminophores, ensuring an average visible transmission >55% and a color rendering index >70. Furthermore, double‐ and triple‐stacked LSC configurations and single LSCs with two‐ or three‐embedded luminophores are optimized. All tested LSC configurations are found to be limited to a power conversion efficiency of around 1% for window‐appropriate transparencies.